Shaka Zulu, visual history and television - Tomaselli, K. G. (Southern African Humanities, 2021)
The paper deals with the television series, Shaka Zulu, made by the South African Broadcasting Corporation in 1985. Production issues, international reception, and visual construction of history are discussed in relation to political issues at the time of its release, and in terms of changing attitudes towards the series as reflected in comment generated about the series' rebroadcast in South Africa during 2001. The way that the series has contributed to myth-making about Zuluness is also discussed. To cite this article: Tomaselli, K. G. 2003. Shaka Zulu, visual history and television. Southern African Humanities 15: 91-107.